2019
DOI: 10.1111/hepr.13344
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA miR143HG predicts good prognosis and inhibits tumor multiplication and metastasis by suppressing mitogen‐activated protein kinase and Wnt signaling pathways in hepatocellular carcinoma

Abstract: Aim The expression of microRNA143HG (miR143HG) was significantly downregulated in hepatocellular carcinoma (HCC) tissues by bioinformatics analysis. This study aimed to determine the role of miR143HG in HCC cell proliferation and metastasis. Methods Fifty patients with HCC were divided into two groups based on median miR143HG expression levels. The correlation between miR143HG expression and prognosis, and the correlations between miR143HG expression and the patients’ clinicopathological characteristics were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Over-expression of CARMN was associated with good prognosis. Generally, this gene contributes to development and progression of HCC by blocking the MAPK and Wnt signaling pathways 58 . EPB41L4A-AS1 (also known as TIGA1) is a p53-regulated gene.…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of CARMN was associated with good prognosis. Generally, this gene contributes to development and progression of HCC by blocking the MAPK and Wnt signaling pathways 58 . EPB41L4A-AS1 (also known as TIGA1) is a p53-regulated gene.…”
Section: Discussionmentioning
confidence: 99%
“…it has been shown that miR-146a not only has a tumor-suppressive effect, but also plays a critical role in the growth of HCC cells and that genetic variation of miR-146a may be a risk factor for developing Hcc (21). The expression of mir143HG was significantly downregulated in HCC cells and tissues, and was associated with the staging and prognosis of patients with Hcc (22). Furthermore, previous research has also suggested that the upregulation of miR-21-5p may be a functional regulator of HCC apoptosis and could be a new tumor marker for early diagnosis of HCC (23).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies characterized the miRNA expression profiles related with growth and metastasis and prognosis of HCC, and dysregulation of miRNAs plays a vital role in hepatic carcinogenesis 17,18. miRNAs could act as potential biomarkers in HCC 19.…”
Section: Discussionmentioning
confidence: 99%